2001
DOI: 10.12968/hosp.2001.62.6.1592
|View full text |Cite
|
Sign up to set email alerts
|

Career success after flexible training in psychiatry: a survey of former flexible trainees in the Thames regions

Abstract: This article outlines the findings of a study which indicate that flexible training in psychiatry was considered adequate to prepare doctors for both full-time and part-time work and that those wishing to work part time had no difficulty in finding jobs after accreditation. However, there was evidence to suggest that part-time consultants experienced more problems and less job satisfaction and that part-time training and working may restrict opportunities for an academic career.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…denied them opportunities to progress (in this, our study agrees with Etchegoyen et al, 2001). Unsurprisingly and overwhelmingly, family reasons are primary in the decision to train flexibly.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…denied them opportunities to progress (in this, our study agrees with Etchegoyen et al, 2001). Unsurprisingly and overwhelmingly, family reasons are primary in the decision to train flexibly.…”
Section: Discussionsupporting
confidence: 88%
“…This project builds on a survey carried out in the Thames region (Etchegoyen et al, 2001), which found that part-time training for women in this region was largely considered satisfactory, although not without difficulties. The national study described here extends the College Research Unit's existing workforce planning research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the Calman reforms, trainees who have reached their CCST are given the 6-month 'grace period' that applies to full-time doctors to find a consultant job. Although it has been argued that a 'pro rata grace period' may be fairer, a recent study (Etchegoyen et al, 2001) found that most trainees had no difficulty in obtaining a consultant job shortly after accreditation.…”
Section: Educational Approvalmentioning
confidence: 98%